Pengembangan Kurikulum Kewirausahaan di Sekolah Menengah Pertama - Yudha Nata Saputra (Jurnal Pendidikan dan Kebudayaan, 2011)
The purpose of writing of this article is to analysis of entrepreneurship in junior high school curriculum development related to the definition of entrepreneurship curriculum, the foundation of entrepreneurship curriculum design, curriculum development in entrepreneurship and entrepreneurial values contained in the curriculum of entrepreneurship. Developing entrepreneurship curriculum into something that is important in order to reduce unemployment in the country and improve peopleâ€™s welfare. Junior high school is a strategic place for the development of entrepreneurship curriculum because at this developmental stage, students already have the ability to think is so very full of potential for them to absorb and apply the values of entrepreneurship in their learning experience.Â ABSTRAKTujuan penulisan artikel ini dimaksudkan untuk mengkaji pengembangan kurikulum kewirausahaan di SMP yang berkaitan dengan definisi kurikulum kewirausahaan, landasan penyusunan kurikulum kewirausahaan, desain pengembangan kurikulum kewirausahaan dan nilai-nilai kewirausahaan yang dimuat dalam kurikulum kewirausahaan. Pengembangan kurikulum kewirausahaan menjadi sesuatu yang penting dalam rangka mengurangi pengangguran di negeri dan meningkatkan kemakmuran rakyat. Tingkat SMP merupakan tempat yang strategis untuk pengembangan kurikulum kewirausahaan karena pada tahap perkembangan ini, siswa sudah memiliki kemampuan berpikir yang lengkap sehingga amat potensial untuk mereka bisa menyerap dan menerapkan nilai-nilai kewirausahaan dalam pengalaman belajar mereka.